2022
DOI: 10.1021/acs.jafc.1c08375
|View full text |Cite
|
Sign up to set email alerts
|

Nuciferine Inhibits TMEM16A in Dietary Adjuvant Therapy for Lung Cancer

Abstract: Lung cancer is a malignant tumor with the highest morbidity and mortality rates. Food therapy is a common adjuvant treatment for lung cancer due to its safety and painlessness. Developing new functional food and exploring novel drug targets is important for lung cancer adjuvant therapy. This study confirmed that the active ingredient nuciferine of the lotus leaf was a novel TMEM16A inhibitor by whole-cell patch clamp experiments and site-directed mutagenesis experiments. CCK8 assay, colony formation assay, wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Dietary adjuvant therapy is widely accepted by patients because of its painlessness, low cost, and high safety . On one hand, dietary adjuvant therapy provides enough nutrition for patients to enhance their own immunity; on the other hand, it inhibits the growth of cancer cells by adding functional food into the diet of patients.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Dietary adjuvant therapy is widely accepted by patients because of its painlessness, low cost, and high safety . On one hand, dietary adjuvant therapy provides enough nutrition for patients to enhance their own immunity; on the other hand, it inhibits the growth of cancer cells by adding functional food into the diet of patients.…”
Section: Introductionsupporting
confidence: 52%
“…Currently, a variety of TMEM16A inhibitors have been confirmed to exhibit anticancer activity . Studies shows that TMEM16A inhibitors T16A inh -A01, CaCC inh -A01, eugenol, and avermectin B1 can inhibit different tumor growth in vitro or in vivo to varying degrees .…”
Section: Introductionmentioning
confidence: 99%
“…Lotus is widely distributed worldwide, and its dried leaf is used as herbal medicine for the treatment of obesity and hyperlipidemia. NF, mainly obtained from the lotus leaf, has been reported to possess extensive pharmacological activities. , The eco-friendly extraction and purification methods of NF are well established, and the purity of NF can be improved to >98%. , Therefore, it is practicable to use NF as a functional food ingredient for disease prevention. Our previous study showed that the efficacy of NF in preventing NAFLD was mainly attributed to mitigated hepatic steatosis and improved the intestinal barrier, specifically by inhibition of weight gain, reduction of hepatic triglyceride and cholesterol levels, increase of SCFA levels, as well as reduction of intestinal permeability and serum LPS, with these beneficial effects attributed in part to histopathological analysis and molecular marker-based assays of the TLR4/MyD88/NF-κB signaling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Duo, et al also reported matrine is an effective and safe TMEM16A inhibitor in vitro and in vivo [ 118 ]. Bai, et al reported administration of nuciferine, a novel TMEM16A inhibitor, significantly enhanced the cancer therapy effect of cisplatin and counteracted the toxicity of high concentrations of cisplatin [ 119 ]. Ani9 is reported to inhibit the proliferation of TMEM16A overexpressed malignant glioma cell [ 120 ].…”
Section: Introductionmentioning
confidence: 99%